Physical and morphological characterization of reactively magnetron sputtered TiN films - Vaz, F. (2002)
The present paper reports the influence of growth conditions on the properties of TiN thin films deposited by rf reactive magnetron sputtering in the low-pressure range. The effects of rf power at the Ti target and the negative bias voltage at the substrate in the morphology, structure, electrical resistivity and colour of the samples were studied in detail. X-Ray diffraction results showed that the delta-TiN phase (a(0) similar to 0.430 nm) is detected in all the samples. The sample prepared with grounded substrate revealed a lattice parameter close to the bulk value (0.424 nm), which is a consequence of a low stress state, due to the absence of ion bombardment. The sample deposited at 1000 W has a lattice parameter of 0.426 nm, close to that of the stress-free material (a(0) =0.424 nm), probably due to some stress relief. All films have a columnar-type structure, lying in the T and I zone of the Thornton Model. The resistivity of the TiN films is almost constant and close to 60 muOmega cm independently of the preparation conditions, except for the films deposited at 1000 W, p similar to 215 muOmega cm, and for the grounded sample, p similar to 153 muOmega cm. These values are probably due to cracks associated with stress relieves, in the first case, and the lack of ion bombardment that leads to films with lower density and higher number of defects in the second. No significant variations in colour were observed.